The interlanguage pragmatics of Japanese daily greetings by Malaysian learners - Jamila Mohd,; Jamaluddin Aziz,; Musaev, Talaibek (Penerbit Universiti Kebangsaan Malaysia, 2020)
Scholars in pragmatics argue that the teaching of a second language (L2) must pay extra attention to the language forms and expressions within specific cultural contexts. Not being able to use a L2 according to the nature of its cultural context could sometimes lead to misunderstanding and miscommunication. This study aims to explain the interlanguage pragmatic transfer in daily greetings used by Malaysian learners of Japanese. Using a convenient sampling technique, the respondents are 80 Malay students enrolling in a Japanese preparatory program prior to attending Japanese universities. Being competent in using Japanese language in context is therefore crucial for them. This study employs a qualitative research approach using Discourse Completion Tests (DCT) and follow-up interviews. Shleykina’s model of greetings is appropriated and used as the framework which allows data to be categorized into six patterns. The findings show that Malaysian learners chose to use less greetings when they greet their Japanese friends vis-a-vis their Malaysian friends. The types of Japanese greetings they use are mostly greeting expressions from what they have learned in the classrooms. Other casual greetings applied are learned from anime, dramas and Japanese TV programs. This study revealed that some of the Japanese greetings used are actually a direct translation from Bahasa Melayu. This pragmatic transfer has offered two perspectives, which are, success transfer and failure transfer. The results contribute towards the importance of exposure to and the understanding of the cultural context of a target language in choosing appropriate greetings among L2 in interlanguage context.